Enhancing thermal performance in power electronic modules through a novel micro-nozzle model and hybrid nanoparticles with varied shape factors - M. Gholinia; E. Shahcheraghi; M. Pourfallah; M. Javidan (International Journal of Thermofluids)
Temperature uniformity in high-heat-flux electronic devices is an important concern in the field of micro-scale heat transfer. The present study recommends four novel configurations of cone-shaped nozzles to reduce the temperature of Si-IGBT electrical modules. Moreover, the thermal characteristics of working fluid (H2O) improved using a 1 % to 5 % volume fraction of Fe3O4 –Ag (50 % -50 %) nanoparticles with Spherical, Blades, and Lamina synthetic shapes. The constant heat flux ranging from 110 W/cm2 to 240 W/cm2 was considered a boundary condition for the top of the module, i.e. IGBT and the Diode. The simulation was conducted by computational fluid dynamic software ANSYS-FLUENT-18.2 which employed the Realizable k-ε model for turbulence flow. The outputs indicated that the spiral nozzles (Case 4) increase the turbulent kinetic energy (TKE) compared to simple cone-shaped nozzles (Case 1). It was also found that the use of hybrid nanoparticles causes an increase in the cooling of the fluid and moves away from the critical point (393.15 K). On the other hand, the synthetic forms of Lamina have caused a reduction of the temperature by almost 2.3 % relative to other forms of nanoparticles because of their higher thermal permeability.